2017
DOI: 10.3174/ajnr.a5331
|View full text |Cite
|
Sign up to set email alerts
|

Value of Thrombus CT Characteristics in Patients with Acute Ischemic Stroke

Abstract: on behalf of the MR CLEAN investigators ABSTRACT BACKGROUND AND PURPOSE: Thrombus CT characteristics might be useful for patient selection for intra-arterial treatment. Our objective was to study the association of thrombus CT characteristics with outcome and treatment effect in patients with acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…For endovascular recanalization therapy, most studies examining the association between perviousness and thrombectomy outcomes have concluded that patients with pervious clots are more likely to be successfully recanalized and will have better outcomes. However this notion has been refuted in at least one subsequent study 6 20 21. By correlating the TAI with clot composition, our study offers a histologic explanation for the association between clot perviousness on imaging and favorable outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…For endovascular recanalization therapy, most studies examining the association between perviousness and thrombectomy outcomes have concluded that patients with pervious clots are more likely to be successfully recanalized and will have better outcomes. However this notion has been refuted in at least one subsequent study 6 20 21. By correlating the TAI with clot composition, our study offers a histologic explanation for the association between clot perviousness on imaging and favorable outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies did not find a relationship between clot size, volume or density, and the efficacy of endovascular treatment. 24 Similarly, these parameters were not associated with rapid recanalization in our study or in a previous trial predicting a response to recombinant tPA (tissue-type plasminogen activator) therapy 17 and thus were not selected in our final models. However, due to the automatic calculation of numerous RF, we were able to identify several other imaging biomarkers of the clot associated with a good response to endovascular treatment.…”
Section: Discussionmentioning
confidence: 86%
“…30 Second, the higher incidence of distal occlusions is also associated with smaller ischemic core and better functional outcome. 31,32 Because of our definitions, the thrombus growth group did not include ICA occlusions on CTA, whereas almost one quarter of patients on the stable group had such ICA occlusions. This may explain why there was also a trend towards better functional outcome on patients with thrombus growth and why this association was lost when only M1 initial target occlusion was included on both groups.…”
Section: Discussionmentioning
confidence: 99%